Haunted spaces, failing myths: Spatial ecology and the collapse of environmental imagination in Indonesian horror cinema - Chintya Angesty; Muhammad Fauzi (Life and Death: Journal of Eschatology, 2026)
Background: The dystopian narrative that has long been used as a source of fear in Indonesian horror films has not been able to reduce the rate of environmental destruction. This phenomenon shows a gap between imagination and ecological awareness. This study attempts to address the failure of ecological myths through Indonesian horror film narratives in changing people's social behavior. Using Lefebvre's theory of the production of space, this study analyzes how haunted spaces are constructed as ideological arenas that reinforce fear without producing ecological reflection. This study aims to reveal how Indonesian horror cinema produces ecological spaces that are trapped in mysticism, and offers a new reading of the failure of Indonesian visual culture in building a critical ecological subjectivity. Methods: This study employs a qualitative design. Data were drawn from secondary sources in the form of Indonesian horror films released over the past two decades. Analysis involved repeated viewing and systematic note taking, with interpretations cross validated against ancillary sources. Findings: Analysis of three Indonesian ecological horror films, namely Angkerbatu (2007), Eva: Pendakian Terakhir (2025), and Kereta Berdarah (2024) shows that ecological space is represented in symbolic and mystical rather than reflective terms. Environmental issues are reduced to religious morality and local myth, and the relationship between humans and nature remains hierarchical and anthropocentric, reinforcing ritual ecology instead of encouraging a post-fear ecology. Indonesian cinematic space functions less as lived space and more as perceived space governed by the logics of industry, myth, and religion. Conclusion: These findings indicate that the failure to construct an ecological imagination is not merely a cinematic shortcoming but a reflection of social structures that struggle to envision nature beyond sacred or supernatural frames. Novelty/Originality of this article: The article advances a new reading of Indonesian horror cinema by integrating spatial production theory with cultural ecology and by introducing ritual ecology as a form of stagnant ecological consciousness. In doing so, it charts a new direction for ecocriticism and Southeast Asian cinema studies, showing how myth and fear configure an environmental imagination that resists reflection.